INVESTIGATION INTO THE PROBLEM OF CHARACTERIZATION OF THE HF IONOSPHERIC FLUCTUATING CHANNEL OF PROPAGATION: CONSTRUCTION OF A PHYSICALLY BASED HF CHANNEL SIMULATOR - Gherm V.E.; Zernov N.N.; Strangeways H.J. (My University, 2004)
A wideband HF simulator has been constructed that is based on a detailed physical model. It can generate an output giving a time realization of the HF wideband channel for any HF carrier frequency and bandwidth and for any given transmitter receiver path, time of day, month and year and for any solar activity/geomagnetic conditions. To accomplish this, a comprehensive solution has been obtained to the problem of HF wave propagation for the most general case of a 3D inhomogeneous ionosphere with time-varying electron density fluctuations. The solution is based on the complex phase method (Rytov s method), which has been extended to the case of an inhomogeneous medium and a point source of the field. Results of simulation obtained according to the technique developed have been presented, calculated for a single-hop path 1000 km long oriented to the south from St. Petersburg and including a horizontal electron density gradient present in the IRI model used as the basis of the ionosphere model. The fluctuations of the ionospheric electron density were characterized by an inverse power law anisotropic spatial spectrum. For this model, the random walk of the phasor at the receiver is determined and shown both for paths reflected in the E- and Fregions, being significantly larger for the latter. The oblique sounding ionogram is constructed and reveals three propagation modes: the E-mode and low and high angle F-mode paths. The time-varying field due to each of these paths is then summed at the receiving location enabling the calculation of the scattering function and also the time realization of the received signal shown as a function of both fast and slow time. This is performed both with and without the presence of the geomagnetic field; in the former case the splitting of the F2-mode into both e- and o-modes is seen. It is also shown how the scattering function can be obtained from the time realization of the channel in a way akin to experimental determination of the scattering function from channel measurements. Results from the simulations show the very significant effect of irregularities of even modest magnitude and the comparative effects due to background ionosphere dispersion and the fluctuating irregularities as well as geomagnetic mode splitting. Since the simulator is based on a physical model, it should be possible by comparison of experimental results and simulation to identify the correspondence between physical parameters (e.g., the variance and anisotropy of the electron density fluctuations, orientation of the propagation path to the magnetic meridian, bulk ionosphere motions) with observed channel parameters (e.g., Doppler spread and shift, time delay spread).